Development of Human Resources in Science and Technology – Experience from the United States and Application in Vietnam - Thạch, Trịnh Ngọc; Thủy, Đào Thị Thu (VNU Journal of Science: Policy and Management Studies; Vol 32 No 1, 2016)
Abstract: In the modern society, human resource is the most vital source for the development of every nation, race or ethnicity because only qualified people can properly manage other sources. Therefore, many countries in the world have implemented policies to enhance domestic human resource and attract high-quality workers from other countries. In order to help the economy of a country integrate with international organizations, it is essential to mention the important role of science and technology work forces. The training and developing high quality human resource has become a top mission in many countries and the United States (US) has become the leading country in the field. Keywords: Human resources, science and technology work forces, experience, United States.